FACTORS RELATED TO DECISION-MAKING WITHIN INTERPROFESSIONAL TEAMS: A SCOPING REVIEW EXTENDED TO AN ONLINE ENVIRONMENT - Tanya N. Beran; Emma Donnelly; Michelle Drefs; Christine A. Walsh; Kate Lupo-Flewelling (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This scoping review provides a comprehensive synthesis of the various factors associated with interprofessional team decision-making. This review is unique in that it includes a broad number of factors relevant to a variety of health settings and professionals involved in team decision-making. Arksey and O’Malley’s methodological framework was used to explore empirical studies following the established protocol. First, clearly developed and inclusive search criteria were specified to find studies on interprofessional team decision-making. This review located 34136 abstracts; a total of 218 met the inclusion criteria. Second, the variety of factors were classified broadly as occurring at the individual, interpersonal, and organizational levels. These factors were further grouped as individual: attitudes, gender, expertise, personality characteristics, and professional identity; interpersonal: communication, coordination, hierarchy, leadership, role definition, shared understanding, team characteristics; and organizational: evaluation and feedback, organizational structure/culture, procedures, and resources. Our next study draws on these findings to determine how decision-making occurs in an online case consultation environment. Specifically, our goal is to examine the role of expertise and hierarchy, found in our scoping review to affect decision-making. Social work and school psychology students (low expertise) will be invited to participate in online case consultations. Upon hearing an incorrect diagnosis given by students in other professional programs, including medicine (higher status hierarchy), we will observe whether they change their correct diagnosis to the same incorrect one that was stated by another team member. Clinical case consultations are a typical training activity (i.e., occur weekly) and a typical professional activity within all professional fields. Thus, it is important to determine how individual and interpersonal factors might affect clinical decision-making.